Determinasi Keputusan Pembelian Produk Body Lotion Nivea Di Kota Semarang - Aurilia riska hapsari; Imam nuryanto (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of price, brand image and promotion on purchasing decisions for Nivea body lotion products in Semarang City, The population in this study were people in Semarang City who decided to buy Nivea body lotion products. Determination of the number of samples was carried out by purposive sampling method as many as 105 respondents. The research data collection technique was carried out through a questionnaire as well as processed using the Statistical Package for the Social Science (SPSS). The results showed that: (1) price has a positive and significant effect on purchasing decisions, (2) brand image has a positive and significant effect on purchasing decisions, (3) promotion has a positive and significant effect on purchasing decisions.